Behaviour-changing ingredients in soft drinks: an experiment developed by school children in partnership with a research scientist. Issue 1 (2nd January 2017) - Judge, Sarah; Delgaty, Laura; Broughton, Mark; Dyter, Laura; Grimes, Callum; Metcalf, James; Nicholson, Rose; Pennock, Erin; Jankowski, Karl
Abstract: A team of six children (13–14 years old) developed and conducted an experiment to assess the behaviour of the planarian flatworm, an invertebrate animal model, before, during and after exposure to chemicals. The aim of the project was to engage children in pharmacology and toxicology research. First, the concept that exposure to chemicals can affect our nervous systems and alter our behaviour was introduced by the scientist. Then pupils were asked to conduct independent online research on chemicals we consume and used this information to select chemicals of interest. Caffeine and the artificial sweetener aspartame were chosen. As aspartame is broken down in the body, the aspartame metabolites phenylalanine, methanol and aspartic acid were also tested. Pupils assessed flatworm behaviour and determined that phenylalanine and methanol altered behaviour. The experiment demonstrated that chemicals can affect the nervous system and can be used in classrooms to illustrate that chemicals, such as recreational drugs, can alter behaviour. Students found the experiential nature of the programme valuable, appreciated the active components and considered the scientist as an 'expert'. This partnership contributes to academic knowledge in children and provides insight into teaching and raises awareness of the curriculum as a tool of social change.